Bespoke regional blocks for axillary sentinel node biopsy. Issue 10 (October 2021) - Clancy, R; Hemington-Gorse, S; Pope-Jones, S; Jayakumar, A; Beynon, C; Egeler, C; Cubitt, J
Summary: Introduction: Axillary sentinel node biopsy for melanoma is routinely performed under general anaesthesia. Emerging evidence has shown general anaesthetics are associated with increased mortality in the context of the COVID-19 pandemic. In the interest of patient safety, we have designed a series of bespoke axillary regional blocks enabling surgeons to remove nodes up to and including level III without the need for a general anaesthetic. The aim of this study was to assess the feasibility of performing axillary sentinel node biopsy under such blocks. Methods: Approval was granted by the Joint Study Review Committee on behalf of the Research and Ethics Department. Ten consecutive patients having axillary sentinel node biopsy for melanoma were included in this prospective study. Patients completed a Quality of Recovery-15 (QoR15) questionnaire preoperatively and 24 h postoperatively. Discussion: One patient had a positive sentinel node, the remining were negative. A significant reduction in time spent in hospital post-operatively ( p = 0.0008) was observed. QoR15 patient reported outcome measures demonstrated high levels of satisfaction evidenced by lack of statistical difference between pre and post-operative scores ( p = 0.0118). 80% of patients were happy to have a regional block and 90% were happy to attend hospital during the pandemic. Conclusion: ASNB under regional block is safe, negates risks associated with performing GAs during the COVID-19 pandemic and facilitates quicker theatre turnover and discharge from hospital. Collaboration between anaesthetic and surgical teams has enabled this change in practice. There is a learning curve with both patient selection, education and development of technique.